Female Sexual Offenders-an Underexamined Population - Dunton, Creaig Anthony (1933)
Sex crimes are considered to be among the most damaging and heinous forms of social deviance in existence. Besides the acts perpetrated by the offenders, the social stigma attached to being victimized is often just as injurious to the victim. Society sees males as the sole perpetrators of acts of sexual abuse, but this is not the case. The extant literature shows that women, while fewer in number, also perpetrate acts of sexual abuse and assault against other adults and children. This thesis is a preliminary typology that classifies female sexual offenders based upon the acts perpetrated, using cases presented in the extant literature. The pre-existing typologies that have been developed come largely from the psychiatric community, and therefore are classified on motivation rather than acts. While this is by no means a complete typology, it is an essential first step in learning more about this underexamined population